Analisis perbandingan kinerja keuangan perusahaan sub sektor farmasi sebelum dan sesudah pandemi covid-19 - Susi Susanti; Aris Munandar; Hanifah Muthiah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The purpose of this study is to determine and compare the financial performance of pharmaceutical sub-sector companies before and after the Covid-19 pandemic. This study uses a comparative type of research using quantitative data from secondary data sources. The research instrument used is a table containing variable indicators Current Ratio (CR), Debt to Equity Ratio (DER) and Return On Assets (ROA). The population used in this study is the financial statements of 13 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. The sample in this study is the financial statements of 6 pharmaceutical sub-sector companies. The sampling technique used in this study is purposive sampling. Data collection techniques used are documentation and literature studies and use data analysis Normality test Then the data will be analyzed using descriptive statistics and to test the difference in financial performance before and after the COVID-19 pandemic, a different test is used: Paired Sample t-Test. The results of the study showed that there was a difference in the Current Ratio (CR) in pharmaceutical sub-sector companies before and after the Covid-19 pandemic, while there was no difference in the Debt to Equity Ratio (DER) and Return on Assets (ROA) in pharmaceutical sub-sector companies before and after the Covid-19 pandemic.